Gender inequities and global health outcomes - Dominic E Madell; Brooke P Hayward (Inishmore Laser Scientific Publishing Ltd, 2019)
Gender has a great impact on the health of some of the most vulnerable populations in the world. Cultural biases against females result in: female infanticide, a lack of female immunisation, malnourishment due to neglect in infancy, sexual and physical violence resulting in injury and sexually transmitted disease, female genital mutilation/ cutting (FGM/C), mental illness, and health systems that do not adequately meet female needs. Female health is also damaged by a lack of focus from research, a disproportionate responsibility placed on females for caring for others, and economic and social situations that result in a lack of access for females to healthcare. Men also suffer from cultural expectations which lead them to disregard their own health, indulge in risky behaviours, and become involved in crime or war. Given that gender cuts across so many aspects of health, it is clear that addressing these cultural issues has a huge impact on the health of vulnerable populations. Globally, cultural change must be addressed through education, together with changes to social policy and legal and economic frameworks to increase female empowerment and encourage more equitable treatment.